Orientação e posição da cabeça, escápula e coluna torácica em crianças respiradoras orais - Patricia Dayrell Neiva (2008)
Objective: Mouth breathing is a frequent clinical condition among school-aged children and some studies have correlated this condition with quality of life and postural alterations. Therefore, the aim of the present study was to investigate the orientation of the scapula, thoracic spine and head posture and assessment quality of life among mouth-breathing (MB) children and nasal-breathing (NB) children. Methods: Twenty-one male MB children and 21 male NB children between eight and 12 years of age participated in the study. Data were obtained through a stereophotogrammetry system that uses passive markers over anatomical landmarks to capture the position of the segments. Internal rotation, upward rotation, anterior tilt, scapular elevation and abduction were measured bilaterally as well as thoracic kyphosis, forward head and shoulder protrusion. The AUQEI scale was applied to assess quality of life. Results: Scapular elevation was significantly different between groups. The MB children showed increased of scapula superior position in relation to the NB group No statistically significant differences were found between groups regarding the other angular and linear measurements of the scapula. Ninety-five percent of the NB children had been breastfed, whereas this figure was 58% among the MB children, which was a statistically significant difference. There were statistically significant differences between groups regarding the domains of the AUQEI scale, but considering cutoff both groups are similar. A significant difference between groups was found regarding the body mass index, which was higher among the NB children. Conclusions: Mouth-breathing children showed a pattern of increasing upward rotation angle and have a increased scapular superior position in comparison to nasal-breathing children due probably to the .position of forward head, leading to an alteration in the positioning of the mandible. The similarity in the posture pattern observed in both groups may be attributed to the height/weight development in this age group, as posture changes in order to adapt to new body proportions, regardless of the health condition of the child. Assesment of quality of life is similar in both groups.